Reconstruction of Curriculum Strategy in Strengthening Students' Resilience and Islamic Character (At Mts Nur Rahmat) - Marwah, Rosedah Sa'datul; Sartikah, Sartikah; Alim, Adam Ahmad Syahrul (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2026)
The phenomenon of Fear of Missing Out (FOMO) among Generation Z has become a serious challenge to character education in the digital era, as intensive social media use can trigger social anxiety, weaken self-control, and reduce students' mental resilience. This condition is reflected in the decline of character indicators and the increasing incidence of cyberbullying, adolescent depression, and ethical problems among students in Indonesia. Therefore, strengthening Islamic character education is urgently needed to build students' psychospiritual resilience amid the pressures of digital culture. This study aims to describe and analyze the curriculum reconstruction at MTs Nur Rahmat in integrating academic, spiritual, and Islamic character aspects to build students' mental resilience in facing the FOMO phenomenon. The study employs a qualitative-descriptive approach using the case study method. Primary data were obtained through in-depth interviews with the Vice Chair of the Foundation, the Principal, the Vice Principal for Curriculum, teachers, and boarding school students. Secondary data were collected through curriculum documentation, syllabi, and class schedules. Informants were selected using purposive sampling. Data validity was ensured through the triangulation of sources and techniques, and data analysis used the Miles and Huberman model. The results of the study indicate that the reconstruction of the national curriculum by integrating the pesantren curriculum has introduced elements of exemplary behavior through habitual activities, and the reinforcement of spiritual values plays a crucial role in building student resilience in the digital age.